InSAR observations of ground deformation : application to the Cascades volcanic arc - Parker, Amy Laura (Springer, 2016)
This doctoral thesis applies measurements of ground deformation from satellite radar using their potential to play a key role in understanding volcanic and magmatic processes throughout the eruption cycle. However, making these measurements is often problematic, and the processes driving ground deformation are commonly poorly understood. These problems are approached in this thesis in the context of the Cascades Volcanic Arc. From a technical perspective, the thesis develops a new way of using regional-scale weather models to assess a priori the influence of atmospheric uncertainties on satellite measurements of volcano deformation, providing key parameters for volcano monitoring. Next, it presents detailed geodetic studies of two volcanoes in northern California: Medicine Lake Volcano and Lassen Volcanic Centre. Finally, the thesis combines geodetic constraints with petrological inputs to develop a thermal model of cooling magma intrusions. The novelty and range of topics covered in this thesis mean that it is a seminal work in volcanic and magmatic studies.- Resumé vydavatel
"Doctoral thesis accepted by University of Bristol, UK."
Keywords: vědy o atmosféře; vulkanologie; geodezie -- Kalifornie severní; atmospheric sciences; volcanology; geodesy -- California, Northern; elektronické knihy; monografie; electronic books; monographs